Tinnitus Suppression with Electrical Stimulation at the Most Basal Contact of the Cochlear Implant Electrode as a Model for Round Window Stimulation - Kiana Kheirkhah; Valerie Van Kelecom; Marc Leblans; Joost van Dinther; Glynnis De Greve; Erwin Offeciers; Andrzej Zarowsk (Journal of International Advanced Otology)
Background: The objective of this research was to test whether efficient tinnitus suppression could be achieved by electrical stimulation of the single most basal electrode contact of a cochlear implant. This approach simulates the effects of electrical stimulation using a round-window electrode.